2008
DOI: 10.7883/yoken.jjid.2008.393
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of <i>Staphylococcus aureus</i> Isolates Carrying Panton-Valentine Leukocidin Genes in Bangladesh

Abstract: To assess the spread and genetic characteristics of Panton-Valentine leukocidin (PVL) gene-carrying Staphylococcus aureus in Bangladesh, we investigated 59 strains (49 isolates from clinical specimens and 10 isolates colonized in the nasal cavities of medical staff), including 26 methicillin-resistant S. aureus (MRSA) strains. The PVL gene was detected only in methicillin-susceptible S. aureus (MSSA) strains (7 clinical strains and 2 colonizing strains). PVL gene-positive MSSA strains were found to belong to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Subarna Roy et al from India, have reported an overall 62.85% of PVL prevalence among MRSA and MSSA (MRSA: 85.1% and MSSA: 48.8%) [ 49 ]. Other parts of the world reported a lower prevalence of PVL (5% in France, 4.9% in the UK, 8.1% in Saudi Arabia, and 14.3% in Bangladesh [ 17 , 50 , 51 , 52 ]), indicating that the prevalence of PVL varies greatly between geographical locations and populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subarna Roy et al from India, have reported an overall 62.85% of PVL prevalence among MRSA and MSSA (MRSA: 85.1% and MSSA: 48.8%) [ 49 ]. Other parts of the world reported a lower prevalence of PVL (5% in France, 4.9% in the UK, 8.1% in Saudi Arabia, and 14.3% in Bangladesh [ 17 , 50 , 51 , 52 ]), indicating that the prevalence of PVL varies greatly between geographical locations and populations.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed no significant difference between MRSA and MSSA populations in terms of PVL carriage. In Nepal, Algeria, Bangladesh, Greece, and Romania, the prevalence rates of the pvl gene among MSSA were 26%, 16.4%, 27.3%, 12%, and 14%, respectively [ 46 , 50 , 53 , 54 , 55 ]. In Iran, Shariati et al [ 48 ] reported PVL carriage in 18.8% of MRSA and only 3% of MSSA, which is in line with other studies that reported higher prevalence in MRSA isolates than MSSA [ 1 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus is a Gram-positive bacterium which in normal conditions is commensal in humans and animals, but can easily become pathogenic, causing frequently skin, respiratory, bone, soft tissue and endovascular infections [46]. As S. aureus often develops resistance to multiple antibiotics, namely to β-lactam antibiotics such as methicillin (MRSA strains) [47], this bacterium is one of the major causes of health care and community associated infections [48] [49]. The aPDT experiments were also performed with combinations of PSs 3a-e with potassium iodide (KI), a well-known potentiator of aPDT effect [50].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate from S. aureus bacteremia is believed to exceed those of tuberculosis, human immunodeficiency virus, and hepatitis B. Additionally, methicillin-resistant Staphylococcus aureus (MRSA) presents a significant threat, causing severe infections in healthcareassociated (HAI) and community-acquired (CAI) settings. Methicillin-resistant S. aureus is characterized by the presence of the mecA gene, which codes for the PBP2a protein located within a specific region of the chromosome known as the Staphylococcal cassette chromosome mec (SCCmec) (1)(2)(3).…”
mentioning
confidence: 99%